Developing and Validating the Initial Version of the Robotic Process Automation Maturity Model - Andrzej SOBCZAK (Communications of International Proceedings, 2020)
In a narrower sense RPA (Robotic Process Automation) can be perceived as one of the categories of software for the automation of business processes. At the same time, it can be considered as a specific type of organisational and technological change. Assuming the latter sense as crucial from the perspective of the implementation of digitisation of a company, it is necessary to carry out a periodic assessment of the maturity of an organisation in terms of RPA. Thanks to such an assessment, it is possible to determine the current advancement of an organization in this regard, but also to determine the improvement activities required for the implementation. However, it is necessary to use an appropriate research tool to carry out such an assessment. The goals of this article include: (G1) presenting the understanding of the term robotic process automation, (G2) describing the building blocks of the maturity model, (G3) presenting the proprietary robotic process automation maturity model and its initial verification.
Keywords: Maturity Model; Robotic Process Automation; RPA; Robotic Process Automation Maturity Model; MORPH